Spatial patterns of evapotranspiration distribution in palm oil plantation - YAZID ISMI INTARA; ABIMANYU DIPO NUSANTARA; SUPANJANI SUPANJANI; ZULBAHRUM ZULBAHRUM CANIAGO; RISKA EKAWITA (Nusantara Bioscience, 2019)
Intara YI, Nusantara AD, Supanjani, Caniago Z, Ekawita R. 2019. Spatial patterns of evapotranspiration distribution in palm oil plantation. Nusantara Bioscience 11: 1-7. Evapotranspiration can directly calculate by some climatic factors which are processed in the form of simulation modeling of two-dimensional evaporation distribution on specified coordinates. This research had been conducted in palm oil plantation PT. Bio Nusantara Bengkulu, Indonesia. The sampling location covered some areas named as TM2, TM22, Palm oil-Field, Palm oil-Residential Area and Palm oil-Secondary Forest. The TM2 and TM22 were a location of palm oil plantation used for 2 and 22 years planting respectively. The three remaining locations dedicated to areas of which mix TM22 with soccer Field, Residential Area and Secondary Forest. The results showed that in palm oil plantation TM 2 which consisted of herbaceous plants and bushes produced more water vapor. At palm oil plantation TM 22 which had fully developed canopy or the entire soil area had been covered by canopy, so only transpiration occurred at this site, less water vapor was produced. This is due to the temperature condition is inversely proportional to the relative humidity. As a comparison of a palm oil plantation evapotranspiration measurement result, indicated on area of football field where only has grass in the field, with low intensity of light, wind, and humidity, affected directly to high amount of evapotranspiration, therefore, more water vapor produced. The measurement result of palm oil plantation nearby residential area showed that the area which consisted of herbaceous plants and bushes, also zinc-roofed residential with the intensity of light and wind directly hit the area, produced less water vapor. Moreover, the condition at the border area between TM 22 and the palm oil secondary forest contained mixed plantation. The measurement result showed that the palm oil secondary forest had the same height of canopy and almost had equal humidity (>76%), but secondary forest plants had more dense plantation density which produced less water vapor.